Assessment of Nodulation Potential of Bradyrhizobium japonicum and Bradyrhizobium elkanii on Glycine max L. in Acidic Clay and Loam Soils - Bobo, Enetia D; Jinga, Percy; Muzvidzwa, Nicole; Zingoni, Girlie; Munosiyei, Pias; Zingoni, Emmanuel (International Journal of Scientific Research in Biological Sciences, 2020)
Poor soils and prohibitive cost of nitrogen fertilizers contribute to low soybean production in southern Africa. Soybean is a legume with high nitrogen demand during its development and is sensitive to acidic soils. This paper investigated the potential of two rhizobia species Bradyrhizobium japonicum strain 550 and Bradyrhizobium elkanii strain 510 in nodulating soybean variety SeedCo Status in acidic clay and loam soils. Strains of Bradyrhizobiun japonicum and B. elkanii rhizobia were each inoculated to surface sterilized soybean seeds prior sowing in acidic clay and loam soils. The inoculated seeds were sown in 1-litre pots with three replicates for each of six treatments. The soybean plants were evaluated for nodule colour, nodule number, shoot biomass and shoot N content. All means were subjected to ANOVA in STATA version 12.1. The observed nodule colour for plants inoculated with B. japonicum and B. elkanii strains was red brown. The results showed a significant difference in nodule number, shoot biomass and N content among the soybean plants inoculated with the rhizobia in both acidic clay and loam soils (F=9.09 p=0.05). Inoculating soybean seed with B. elkanii strain 510 provides more nodulation potential in acidic loam soil than B. japonicum strain 550 in the same soil type.